Iron(III)‐Selective Chelation‐Enhanced Fluorescence Sensing for In Vivo Imaging Applications. Issue 9 (31st July 2015) - Guo, Lin E.; Liu, Xin Yi; Wang, Huan; Chen, Qiu Ling; Wang, Guang Ke; Luo, Kaijun; Mi, Qi Li; Zhou, Ying; Zhang, Jun Feng
Abstract A "turn‐on" pattern Fe3+‐selective fluorescent sensor was synthesized and characterized that showed high fluorescence discrimination of Fe3+ over Fe2+ and other tested ions. With a 62‐fold fluorescence enhancement towards Fe3+, the probe was employed to detect Fe3+ in vivo in HeLa cells and Caenorhabditis elegans, and it was also successfully used to elucidate Fe3+ enrichment and exchange infected by innexin3 (Inx3) in hemichannel‐closed Sf9 cells.